VD_FINDINFO Décision / 2011 / 503 vom 4. August 2011 - VD Tribunal cantonal (2011)
DÉTENTION PRÉVENTIVE, RISQUE DE RÉCIDIVE, MISE EN LIBERTÉ DÉFINITIVE | 221 CPP (CH), 222 CPP (CH), 228 CPP (CH), 393 al. 1 let. c CPP (CH)